(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the efficacy and safety of low dose (20 mg) isotretinoin for the treatment of mild to moderate acne for a duration of six to nine months. Study Design: This was an observational, non-comparative, uncontrolled study. Place and Duration of Study: This study was carried out at the Department of Dermatology, Shalamar Hospital Lahore from 01-1-2010 to 31-12-2013. Materials and Methods: Six hundred adult patients of either sex with mild to moderate acne and, ages between 15 to 25 years were enrolled. They were treated with a fixed low dose of isotretinoin daily irrespective of weight, for six to nine months. Patients were evaluated clinically at baseline, then monthly during the treatment and follow-up. Results: Of the 600 patients enrolled, 580 completed the study. 94% of patients were completely cured in six months with a cumulative dose of 62.37 mg/kg.Treatment was continuedfor 6 % of patients, who still had active acne lesions.The cure rate reached 98.96 % at the end of ninth months. Patients were followed for another six months and a relapse rate of 4.48% was observed. Mild cheilitis and xerosis were common. Laboratory abnormalities were mild and transient. Conclusion: Six to nine months treatment with a daily dose of 20 mg/day isotretinoin was found to be effective in patients with mild to moderate acne. The drug was well-tolerated and showed almost negligible clinical and laboratory side effects.